IT solutions for health workforce shortages: improving administrative processes and care access—a comparative study of five European countries - Michalska, Kamila; Gonzalez Gonzalez, Ana Isabel; Likic, Robert; Flinterman, Linda; Dan, Sorin; Domagala, Alicja (Oxford University Press, 2025)
The healthcare sector faces a critical shortage of healthcare workers, creating significant challenges in healthcare delivery. The use of Information Technology (IT) solutions in healthcare presents potential remedies to reduce the negative consequences of this problem. The purpose of this study was to identify IT solutions implemented to mitigate the effects of medical shortages and improve administrative processes and care access. The study used a systematic approach integrating desk research, national expert consultations and comparative analysis to examine IT solutions in healthcare systems. Five European countries were selected for the in-depth analysis: Poland, the Netherlands, Spain, Finland, and Croatia. The impact on administrative processes, care access, and the functioning of healthcare systems was assessed. The study identified a variety of regulatory frameworks, common implementation strategies and the institutions responsible for these activities. All compared countries used telemedicine, e-prescriptions and various types of health applications. It was found that the most frequently used IT solutions were electronic health record (EHR) and e-prescription systems. However, IT training, its organization, financing and mandatory nature differed in individual countries. In addition, common barriers were identified across all countries, such as financial constraints and interoperability issues. Integrating IT solutions offers opportunities to address health workforce shortages and enhance healthcare efficiency. Tailored strategies and collaborative efforts are essential to address financial constraints and interoperability issues. Implementing best practices identified in this study can improve administrative processes and care access. Future research should prioritize longitudinal impact assessments and explore new technologies to optimize healthcare IT solutions.
Keywords: Digital health; healthcare workforce; administrative processes; healthcare access; fi=Julkisjohtaminen|en=Public Management|